Moscone/Milk candlelight vigil - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a group of men participating in a candlelight vigil in memory of San Francisco mayor, George Moscone, and San Francisco supervisor, Harvey Milk, who had been assasinated by Dan White.